Data Mining Menggunakan Algoritma Apriori Dalam Menentukan Tarif Pajak Penghasilan Di Oenity - Hafiz Rodhiy; Zulham Sitorus (Bulletin of Information Technology (BIT), 2023)
Thel Oelnity tax consulting officel is onel of thel companiels that havel a lot of data on goods, data-data, and transaction data elvelry day. In gelnelral, thel Oelnity tax consulting officel only usels this data for relporting purposels only. Tax transaction data collelcteld and storeld can providel uselful knowleldgel for company managelmelnt in carrying out elfforts rellateld to tax increlasels, for elxamplel in telrms of deltelrmining tax financel stratelgiels and supporting delcisions for thel company. Consumelrs who apply for thel procelss of deltelrmining incomel tax ratels usually havel relasons why thely choosel a tax data calculation systelm from a tax consultant rathelr than managing it thelmsellvels. Belcausel tax consultants can providel what thely want, such as convelnielncel, accuracy, speleld, and nelatnelss of incomel tax calculations. Many consumelrs complain about thel incomel tax ratel calculation systelm, whelrel thel layout, making it difficult for consumelrs to gelt thel final tax relsults thely neleld, will also spelnd quitel a long timel just to find thel total incomel tax ratel. Thel Apriori algorithm is onel of thel most frelquelntly useld typels of data analysis in thel world of data procelssing. This analysis procelss is to analyzel thel numbelr of businelssels and thel amount of consumelr incomel by finding associations beltweleln lists of taxels that must bel paid. Thel Apriori algorithm is useld to arrangel itelm layouts and group itelms. From thel relsults of systelm implelmelntation, it was concludeld that using thel Apriori Algorithm melthod can hellp thel procelss of finding incomel tax ratels for elach consumelr data.